Countering the double-whammy of zoonotic diseases - Thomas, Lian F.; Patterson, G.; Coyne, L.A.; Rushton, Jonathan (2020)
Estimates put the number of people dying from endemic zoonoses at more than two million each year. Those affected above all belong to the low- and middle-income strata of society who have already been overlooked by both policy-makers and healthcare providers. Our authors give an overview of the key drivers of zoonoses and show how the One Health approach can help to control and prevent zoonotic diseases.